AMPK Promotes Xenophagy through Priming of Autophagic Kinases upon Detection of Bacterial Outer Membrane Vesicles - Losier, Truc T.; Akuma, Mercy; McKee-Muir, Olivia C.; LeBlond, Nicholas D.; Suk, Yujin; Alsaadi, Reham M.; Guo, Zhihao; Reshke, Ryan; Sad, Subash; Campbell-Valois, François-Xavier; Gibbings, Derrick J.; Fullerton, Morgan D.; et al. (Université d'Ottawa | University of Ottawa, 2019)
The autophagy pathway is an essential facet of the innate immune response, capable of rapidly targeting intracellular bacteria. However, the initial signaling regulating autophagy induction in response to pathogens remains largely unclear. Here, we report that AMPK, an upstream activator of the autophagy pathway, is stimulated upon detection of pathogenic bacteria, before bacterial invasion. Bacterial recognition occurs through the detection of outer membrane vesicles. We found that AMPK signaling relieves mTORC1-mediated repression of the autophagy pathway in response to infection, positioning the cell for a rapid induction of autophagy. Moreover, activation of AMPK and inhibition of mTORC1 in response to bacteria is not accompanied by an induction of bulk autophagy. However, AMPK signaling is required for the selective targeting of bacteria-containing vesicles by the autophagy pathway through the activation of pro-autophagic kinase complexes. These results demonstrate a key role for AMPK signaling in coordinating the rapid autophagic response to bacteria.
Keywords: AMPK; OMV; Salmonella; ULK1; VPS34; autophagy; mTOR; outer membrane vesicles; xenophagy